Exploring the transformative role of drama in enhancing English language learning: Benefits, challenges, and strategies - Na’ima, Farisma Nadhrotun; Balqis, Soraya; Rohmana, Wahyu Indah Mala (Maliki Interdisciplinary Journal, 2024)
This article explores the integration of drama in English as a Foreign Language (EFL) classes to enhance language learning. Amidst varied methods of English learning, the focus shifts from traditional teaching approaches to literature, particularly drama. Literature’s educational potential is underscored, encompassing cultural exploration and personal growth. The discussion emphasizes drama’s benefits and challenges in EFL classrooms. Drama not only enhances language acquisition but also boosts pronunciation, vocabulary, and confidence. Challenges include effective planning and addressing student anxieties. In conclusion, drama’s transformative impact on language learning is evident. By fostering creativity, cooperation, and engagement, drama becomes a dynamic tool to enhance language skills. Practical strategies for drama integration are highlighted, advocating for comprehensive preparation and thoughtful execution in EFL classrooms